PENINGKATAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL EXPERIENTAL LEARNING PADA SISWA KELAS V SD - Yolanda, Gita; Mahjuddin, Ritawati; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of narrative writing skill by using experiental learning models at grade V student of Elementary School. The type of research is PTK by using qualitative and quantitative approach. This research was conducted at SD Negeri35 Parak Karakah, Padang city with a total of 22 students consisting of 10 male students and 12 female students. The result of the narrative writing skill in the pre-writing at cycle I 57,8 (C) increases on cycle II 87,5 (SB). The writing phase in the first cycle 48,8 (K), increased in the second cycle 79,7 (B), the post-writing phase cycle I 58,3 (C) increases in cycle II 84,3 (B).  Keywords: Increased, narrative writing, experiental lerning model.